Analysis of the floristic composition of the forests of Jenaro Herrera, Loreto, Peru - N. Honorio, Eurídice (2008)
The floristic composition of 17 plots (0,5 - 2 ha) of Jenaro Herrera, Loreto, Peru were analyzed using the unweighted pair group method with arithmetic mean (UPGMA). Nine floristic groups were reported corresponding to the following types of forests described in the study area before: 1) riverine forest -one group, 2) black water broad leaf forest -two groups, 3) white sand forest -two groups (plus one group with a plot including part of another type of forest), 4) terrace forest -one group, 5) black water palm forest -one group, and 6) low terrace palm forest -one group. Taxonomic problems were detected in species level; however, these were minimized when rare species were removed.